A multi-objective optimization strategy for the optimal control scheme of pumped hydropower systems under successive load rejections. (1st March 2020) - Lai, Xinjie; Li, Chaoshun; Zhou, Jianzhong; Zhang, Yongchuan; Li, Yonggang
Highlights: A refined nonlinear model of PSHSs under successive load rejection is established. Proposing a control scheme optimization strategy for successive load rejections. Successive load rejection parameters have significant impact on the transient process. The optimized control scheme is applicable to various working conditions. The work can strongly support the safe operation of pumped storage hydropower stations. Abstract: Pumped hydropower is the most important sustainable energy in a power grid, which is converted into electricity through pumped storage hydropower systems. The energy conversion process in a pumped storage hydropower system, however, may be greatly threatened by extreme energy conversion conditions, especially successive load rejections. Although successive load rejections have been addressed in previous studies, the optimal control scheme for successive load rejections has not yet been reported. In this study, a refined nonlinear model for successive load rejections is constructed by incorporating a guaranteed calculation for regulation (GCR), and the effects of the rejection parameters on the transient processes of pumped storage hydropower systems are investigated quantitatively based on the refined model. The results show that: (1) the rejection parameters significantly impact the successive load rejections, and the worst working condition of a successive load rejection can be identified by the worst combination of rejection parameters; (2) the rotational speed and the water pressure of the pump storage unit are conflicting objectives with variation in the control schemes. Moreover, a novel two-stage multi-objective optimization strategy for the optimal control scheme of pumped hydropower systems is proposed and a case study is conducted based on a real pumped storage hydropower system in China. Compared with the on-site measurements, the proposed optimization strategy can improve the maximum volute water pressure and the minimum draft tube water pressure by at most 7.6% and 17.4% under the worst working condition of a successive load rejection. Furthermore, it is verified that the obtained optimal control scheme meets the GCR criterion under various working conditions that are not the worst case. These results highlight the effectiveness and availability of the proposed optimization strategy for sustaining the safe operation of pumped storage hydropower systems.